Synthesis, Characterization, Biological Study of Synthesized Lauha Bhasma - Paudel, Rajesh; Karn, Gopinand; Aryal, Girija; Giri, Jyoti; Adhikari, Rameshwar; Sharma, Motee Lal (Journal of Nepal Chemical Society, 2022)
Bhasmas are prepared from metallic and herbal ingredients and are also referred to as herbo-metallic preparations. Lauha bhasma (LB) is one of the iron-based herbo-metallic preparations used in Ayurvedic medicine for treating various ailments due to iron deficiency. The preparation of LB involves normal purification (samanya sodhana), special purification(vishesha sodhana) followed by drying under sunlight (bhanupaka), heating in a frying pan (sthalipaka), and calcination (putapaka) with Triphala kwatha as a medium under the temperature of 650 oC in an electric muffle furnace (EMF) and maintained for 1 hour. LB is subjected to different physicochemical analysis and modern analytical methods using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Spectroscopy (XRD), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX). Prepared LB is also undertaken to antibacterial study and is compared with market samples. The results suggest that organoleptic characters, preliminary test, and the physicochemical result of LB suggest that these steps were necessary to obtain a good quality of bhasma and also make it acceptable during the Bhasmikarna process. From physicochemical analysis data, it was observed the negligible moisture content (0.42 %; loss on drying), total ash value (17.3 %), acid insoluble ash value (7.6 %). It was observed that LB was prepared in 21 puta where the average crystalline size was found to be 57.23 nm from XRD spectra. SEM analysis shows the fine coarse structure with a uniform particle size of LB. EDX graph shows the presence of Fe (75.43 %) as a major element.FTIR spectra suggest the presence of different organic moieties which enhance the therapeutic action due to which bhasma shows significant antibacterial properties.